Daclizumab reverses intrathecal immune cell abnormalities in multiple sclerosis. (7th April 2015) - Lin, Yen Chih; Winokur, Paige; Blake, Andrew; Wu, Tianxia; Romm, Elena; Bielekova, Bibiana
Abstract Objective Novel treatments such as natalizumab and fingolimod achieve their therapeutic efficacy in multiple sclerosis (MS) by blocking access of subsets of immune cells into the central nervous system, thus creating nonphysiological intrathecal immunity. In contrast, daclizumab, a humanized monoclonal antibody against the alpha chain of the IL‐2 receptor, has a unique mechanism of action with multiple direct effects on innate immunity. As cellular intrathecal abnormalities corresponding to MS have been well defined, we asked how daclizumab therapy affects these immunological hallmarks of the MS disease process. Methods Nineteen subpopulations of immune cells were assessed in a blinded fashion in the blood and 50‐fold concentrated cerebrospinal fluid (CSF) cell pellet in 32 patients with untreated relapsing‐remitting MS (RRMS), 22 daclizumab‐treated RRMS patients, and 11 healthy donors (HDs) using 12‐color flow cytometry. Results Long‐term daclizumab therapy normalized all immunophenotyping abnormalities differentiating untreated RRMS patients from HDs. Specifically, strong enrichment of adaptive immune cells (CD4+ and CD8+ T cells and B cells) in the CSF was reversed. Similarly, daclizumab controlled MS‐related increases in the innate lymphoid cells (ILCs) and lymphoid tissue inducer cells in the blood and CSF, and reverted the diminished proportion of intrathecal monocytes. The only marker that distinguished daclizumab‐treated MS patients from HDs was the expansion of immunoregulatory CD56bright NK cells. Interpretation Normalization of immunological abnormalities associated with MS by long‐term daclizumab therapy suggests that this drug's effects on ILCs, NK cells, and dendritic cell‐mediated antigen presentation to CD4+ and CD8+ T cells are critical in regulating the MS disease process.